2020
DOI: 10.1016/j.conctc.2020.100620
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for assessing the user acceptance, safety and efficacy of a tablet-based workflow and decision support system with incorporated basal insulin algorithm for glycaemic management in participants with type 2 diabetes receiving home health care: A single-centre, open-label, uncontrolled proof-of-concept study

Abstract: Introduction Diabetes management can be especially complex for older adults who receive health care at home. Thus, international guidelines recommend basal-insulin regimens due to simpler handling and low hypoglycaemia risk. A basal-insulin algorithm (including basal-plus) was developed to also include participant's health status and subsequently implemented into a tablet-based workflow and decision support system, GlucoTab@MobileCare. This study protocol describes a proof-of-concept study to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This approach may avoid the need for diabetes-related unscheduled patient presentations to practitioners, emergency rooms, or hospitalizations. One of these systems, incorporating a basal algorithm and a basal plus insulin algorithm, was tested within a proof-of-concept study on patients with type 2 diabetes who were receiving domiciliary nursing care under routine conditions [ 23 ]. Preliminary results showed that admissions to the hospital due to hypo- or hyperglycemic derailment is substantially reduced while glycemic control is improved by using this system.…”
Section: Available Telediabetology Solutionsmentioning
confidence: 99%
“…This approach may avoid the need for diabetes-related unscheduled patient presentations to practitioners, emergency rooms, or hospitalizations. One of these systems, incorporating a basal algorithm and a basal plus insulin algorithm, was tested within a proof-of-concept study on patients with type 2 diabetes who were receiving domiciliary nursing care under routine conditions [ 23 ]. Preliminary results showed that admissions to the hospital due to hypo- or hyperglycemic derailment is substantially reduced while glycemic control is improved by using this system.…”
Section: Available Telediabetology Solutionsmentioning
confidence: 99%
“…If participants also received basal-plus insulin therapy, the bolus insulin component was estimated initially with 20% of the basal insulin dose. If necessary, investigators were contacted and reviewed the suggestion for correctness and plausibility ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Second: Support in performing the subcutaneous basal insulin therapy, especially tailored to participants, by providing a) insulin dose recommendations for an initial basal insulin dose and basal insulin titration support based on previous BG values and insulin doses. An authorized healthcare professional must confirm the suggested insulin dose in regular intervals, b) workflow support for varying intensity of BG measurements (full daily profile during therapy initialisation phase versus fasting values only for ongoing therapy), c) workflow support and dose calculation for basal-plus therapy which means administration of a short-acting insulin together with a defined meal ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Proof of concept for the investigation of efficacy, safety, and user’s acceptance of decision support in ambulatory participants receiving home health care is undergoing. 24 More evidence is needed to determine whether CDS for diabetes in the ambulatory setting influences rates of hospitalization or glycemic control achieved during hospital stays.…”
mentioning
confidence: 99%